2021
DOI: 10.1055/s-0040-1722270
|View full text |Cite
|
Sign up to set email alerts
|

Use of Glucocorticoids and Risk of Venous Thromboembolism: A Narrative Review

Abstract: Glucocorticoids are potent anti-inflammatory agents that are widely used for the treatment of many inflammatory, autoimmune, and neoplastic disorders. However, their beneficial effect is associated with several side effects, including an increased risk of cardiovascular complications, such as myocardial infarction and stroke. Whether their use also contributes to a procoagulant state, and therefore increases the risk of venous thromboembolism (VTE), is still a matter of debate. As an increased risk of venous t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 67 publications
2
13
2
1
Order By: Relevance
“…16 Furthermore, there seems to be an association between steroid therapy, which was used by 1/3 of the patients with IBD, elevated FVIII levels and thrombosis. 17 The risk of recurrent thromboembolic events on anticoagulation in our two groups was similar to the low risk reported in a meta-analysis of 26 studies that included patients with first unprovoked VTE and with extended oral anticoagulant treatment, namely 1.41 per 100 patient-years. 18 Furthermore, the risk of recurrent events after discontinuation of anticoagulation was of the same magnitude as the 10.3 events per 100 patient-years (during the first year) in another meta-analysis of 18 studies with patients treated after first unprovoked VTE.…”
Section: Accepted Manuscriptsupporting
confidence: 85%
See 1 more Smart Citation
“…16 Furthermore, there seems to be an association between steroid therapy, which was used by 1/3 of the patients with IBD, elevated FVIII levels and thrombosis. 17 The risk of recurrent thromboembolic events on anticoagulation in our two groups was similar to the low risk reported in a meta-analysis of 26 studies that included patients with first unprovoked VTE and with extended oral anticoagulant treatment, namely 1.41 per 100 patient-years. 18 Furthermore, the risk of recurrent events after discontinuation of anticoagulation was of the same magnitude as the 10.3 events per 100 patient-years (during the first year) in another meta-analysis of 18 studies with patients treated after first unprovoked VTE.…”
Section: Accepted Manuscriptsupporting
confidence: 85%
“… 16 Furthermore, there seems to be an association between steroid therapy which was used by one-third of the patients with IBD, elevated FVIII levels, and thrombosis. 17 …”
Section: Discussionmentioning
confidence: 99%
“…Some investigators have questioned whether the association between glucocorticoid use and VTE can be explained by the underlying disease condition. 20 Majoor et al showed a higher incidence of pulmonary embolism in severe asthma patients than mild-to-moderate patients and concluded that oral corticosteroid use and severe asthma were independent risk factors for pulmonary embolism (HR: 2.82 (1.09–7.30) and 3.33 (1.16–9.93), respectively). 31 Restricting our study to asthma patients only allowed us to control for asthma and to evaluate the independent effect of glucocorticoid use on the risk of VTE.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] Earlier studies conducted among patients with varied indications for glucocorticoid use (including asthma, joint disorders, connective tissue disorders, inflammatory bowel disease, upper and lower respiratory disorders) compared to non-users have shown increases in the risk of VTE. 7,11,[17][18][19][20][21][22] However, it is challenging to tease apart the prothrombotic effect of glucocorticoids from the inflammatory and hypercoagulable state induced either chronically by the disease state or acutely with episodes of asthma exacerbation. In this study, we used a population-based nested case-control study in the United Kingdom Clinical Practice Research Datalink (CPRD) GOLD to evaluate the association between glucocorticoid use in patients with asthma and the risk of developing VTE.…”
Section: Introductionmentioning
confidence: 99%
“…Cases with transient antithrombin deficiency have very recently been described ( 10 , 11 ). Inflammatory processes are always orchestrated by pleiotropic and multifunctional cytokines and chemokines which have pro-thrombotic effects in thrombosis ( 12 ). Previous studies have demonstrated that the coagulation activation markers IL-1β, IL-6, and IL-8 were associated with VTE ( 13 ).…”
Section: Discussionmentioning
confidence: 99%